2015
DOI: 10.3126/ajms.v7i2.12717
|View full text |Cite
|
Sign up to set email alerts
|

A study of angiographic severity in patients with coronary artery disease and hyperuricemia

Abstract: Backgrounds: Hyperuricemia has not yet been established as cardiovascular risk factor. We aimed to study the angiographic severity in patients with coronary artery disease (CAD) and hyperuricemia.Materials and Methods: In this observational cross-sectional study we measured serum uric acid level in 82 patients of CAD who underwent coronary angiography in catheterisation laboratory of our Institution. Severity of CAD was determined on the basis of Gensini score, number of diseased vessels, critical lesions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…The systematic review of the five articles showed a positive correlation between uric acid level and severity of coronary artery stenosis (Gensini score) in ACS patients. 6,[9][10][11][12] the relationship between SUA and severity of coronary atherosclerosis evaluated via endothelial dysfunction using peripheral arterial tone (PAT The secondary outcome demostrated that compared to normouricemia, hyperuricemia in ACS patients was associated with severity, wound area, and total occlusion number. 6,10-number of diseased vessels, critical lesions and total occlusions on coronary angiogram.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review of the five articles showed a positive correlation between uric acid level and severity of coronary artery stenosis (Gensini score) in ACS patients. 6,[9][10][11][12] the relationship between SUA and severity of coronary atherosclerosis evaluated via endothelial dysfunction using peripheral arterial tone (PAT The secondary outcome demostrated that compared to normouricemia, hyperuricemia in ACS patients was associated with severity, wound area, and total occlusion number. 6,10-number of diseased vessels, critical lesions and total occlusions on coronary angiogram.…”
Section: Resultsmentioning
confidence: 99%
“…Berdasarkan hasil telaah sistematis dari kelima artikel, didapatkan adanya korelasi positif antara kadar asam urat serum dengan keparahan stenosis arteri koroner (skor Gensini) pada pasien SKA. 4,9,[16][17][18] Hasil luaran lain dari telaah sistematis ini menunjukkan bahwa normourisemia pasien dengan hiperuresemia pada pasien SKA berhubungan dengan keparahan, luas lesi dan jumlah oklusi total arteri koroner. 9,[16][17][18] Hasil telaah sistematis didapatkan lima penelitian yang layak untuk dianalisis menggunakan program CMA3, untuk melihat korelasi kadar asam urat serum dengan skor Gensini.…”
Section: Hasilunclassified
“…Masingmasing penelitian mencantumkan data karakteristik dasar faktor risiko kardiovaskular termasuk hipertensi, diabetes melitus, dislipidemia, 4,9,17 dan merokok. 4,9,16,17 Namun, pada penelitian lain mengeklusi diabetes melitus 16,18 ataupun hipertensi 16 dalam penelitiannya. Masing-masing penelitian juga menunjukkan perbedaan persentase tipe klinis pasien SKA baik UAP, NSTEMI, dan STEMI, 9,[16][17][18] sedangkan satu penelitian lainnya hanya meneliti pasien SKA dengan tipe klinis UAP dan NSTEMI.…”
Section: Hasilunclassified
See 1 more Smart Citation
“…Hyperuricemia is a metabolic disease with increased serum uric acid levels as a result of increased uric acid formation or reduced uric acid excretion by the kidneys, or both ratiwi (Maruhashi T, 2013) (Thottam et al, 2017). Hyperuricemia is not only a risk factor for gout, but also a major determinant of hypertension, diabetes mellitus, chronic kidney disease, and cardiovascular disease (Kim et al, 2018) (Pramanik et al, 2015). Several studies have shown a significant role of hyperuricemia in the occurrence of vascular endothelial dysfunction which is the main mechanism in triggering atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%